Green-Samoilenko function and existence of integral sets of linear extensions of nonautonomous equations - Asrorov, F. A.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
An integral invariant set is constructed for systems of differential equations by using the Green-Samoilenko function. The problem of asymptotic stability of this set is studied.